1983
DOI: 10.1088/0029-5515/23/1/013
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Physics and Controlled Nuclear Fusion Research (Report on the 9th IAEA International Conference, Baltimore, 1982)

Abstract: During the past decade of IAEA Conferences on controlled fusion research, the topic of principal interest has shifted from the feasibility of fusion power to the optimization of economically favourable reactor characteristics: efficient plasma heating systems, high beta values, quasi-steady-state operating capabilities, simple coil structures, etc. At the present Conference, the experimental tokamak papers (about half the total number of papers in the category of magnetic-confinement experiments) offer a strik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
89
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(95 citation statements)
references
References 1 publication
6
89
0
Order By: Relevance
“…In passing, we remark that the trapped ion radial width modification due to E r shear [53][54][55][56] is on the order of unity for our ordering based on typical tokamak H-mode edge plasma parameters. This can be easily shown from the fact that in general toroidal geometry, the banana orbit modification parameter 57 is given by…”
Section: Shearmentioning
confidence: 78%
“…In passing, we remark that the trapped ion radial width modification due to E r shear [53][54][55][56] is on the order of unity for our ordering based on typical tokamak H-mode edge plasma parameters. This can be easily shown from the fact that in general toroidal geometry, the banana orbit modification parameter 57 is given by…”
Section: Shearmentioning
confidence: 78%
“…Neoclassical ion transport is important in stellarator plasmas, because the helical ripple losses are comparable to or sometimes even higher than the anomalous losses in contrast to those in tokamaks. The crucial issues of neoclassical ion transport are (1) the reduction of ion thermal diffusivity due to a large positive radial electric field in the electron root [1][2][3], and (2) the reduction of ion thermal diffusivity due to the optimization of the magnetic field structure (s optimization) [3][4][5][6]. However, there has been no experimental study to test these issues on the neoclassical ion transport in stellarator plasmas.…”
mentioning
confidence: 99%
“…In the limiter configuration it is also observed that the potential behind the limiter correlates well with the time variation of T i (0). Thus we expect that one of the candidates for the mechanism for improved ripple ion confinement is the E r × B rotation [21] and orbit squeezing effect due to the electric field and its shear [22,23]. Preliminary orbit calculations show that protons at E = 10 keV with v ≈ 0 can be confined using a model of the potential profile whose peak value is ∼ −1 keV and strong electric shear near the edge.…”
Section: Ion Heating and Transport Improvementmentioning
confidence: 99%